Transcription of herpes simplex virus genes in vivo: overlap of a late promoter with the 3' end of the early thymidine kinase gene. - Sharp, J A (1983)
We identified in herpes simplex virus type 1-infected cells six cytoplasmic transcripts which were complementary to BamHI restriction endonuclease fragment Q. Two transcripts appeared in major amounts compared with the other four. One major transcript of about 1.4 kilobases was the mRNA for the viral thymidine kinase, was synthesized at intermediate times, and was classified as a beta transcript. The other major transcript was synthesized at late times and was classified as a gamma transcript. This late transcript was about 3 kilonucleotides long and was transcribed in the same direction as the gene for thymidine kinase. The 5' end of this late RNA was located by RNA sequence analysis and was 23 nucleotides downstream from the polyadenylation site for the thymidine kinase mRNA. This finding led to the conclusion that the control region for the 3-kilobase gamma transcript is contained within the 3' untranslated region of the thymidine kinase transcript.